Balancing acts – striving towards independence after early discharge: lived experiences of older adults and their relatives - Aline Dragosits; Bente Martinsen; Ann Hemingway; Annelise Norlyk (BMC Health Services Research)
Abstract Background Early hospital discharge is rising internationally. Hence, homecoming is a significant event that has a severe impact on the well-being of older adults and their relatives. Evidence suggests that adapting to this unfamiliar situation requires a concerted effort to strive towards independence. This study describes the meaning of striving towards independence as experienced by older adults and their close relatives during the first month after early discharge from hospital to home and examines how this process relates to their experiences of well-being. Methods Data was gathered through 18 dyadic phenomenological in-depth interviews with ten older adults discharged from three hospitals in Austria and their relatives. Results The essential meaning of striving towards independence after early discharge is characterised by being at ease and further articulated in the three constituents: walking a tightrope between push and support, steady improvement as an opportunity for new possibilities and returning to cherished habits as a source of joy in life. Conclusion Our study highlights the dynamic process of striving towards independence, which encompasses acceptance, trust and identification with the condition, and is intertwined with existential dimensions of temporality, inter-subjectivity and identity. Facilitating trust in the future between the older adult and their carers, as well as helping them regain former habits, supports the strive towards independence after early hospital discharge and contributes to the experiences of well-being of older adults and relatives.